1976
DOI: 10.1029/gl003i003p00205
|View full text |Cite
|
Sign up to set email alerts
|

Matched filtering for the seismic moment tensor

Abstract: By a process of matched filtering it is possible to deconvolve a small number of acceleration or strain records for the moment rate tensor of a seismic source. Theoretically, one horizontal accelerometer (or strain meter) or two vertical accelerometers is sufficient. Practically, five to ten records can be shown to suffice. Specifically, the mechanism of the Colombian event of July 31, 1970 can be retrieved from a sparse network of ten WWSSN vertical instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…We are helped in this respect by the fact that robust moment tensors can be obtained from relatively sparse datasets. Buland and Gilbert [9] showed that it is at least theoretically possible to invert a single, non-naturally rotated horizontal record into the full time history of the moment tensor, and Ekström et al [20] demonstrated that it was feasible to invert a static moment from a three-component record at a single digital broad-band station. Of course, the situation deteriorates when working with analog data (WWSSN or older), since the narrower response of the instruments acts as a de facto filter on the dataset and reduces its resolution.…”
Section: Golitsyn Ew 24 April 1916mentioning
confidence: 99%
“…We are helped in this respect by the fact that robust moment tensors can be obtained from relatively sparse datasets. Buland and Gilbert [9] showed that it is at least theoretically possible to invert a single, non-naturally rotated horizontal record into the full time history of the moment tensor, and Ekström et al [20] demonstrated that it was feasible to invert a static moment from a three-component record at a single digital broad-band station. Of course, the situation deteriorates when working with analog data (WWSSN or older), since the narrower response of the instruments acts as a de facto filter on the dataset and reduces its resolution.…”
Section: Golitsyn Ew 24 April 1916mentioning
confidence: 99%
“…The extension to surface waves has been proposed by a number of investigators (Buland & Gilbert 1976;McCowan 1976;Mendiguren 1977). This paper uses the frequency domain inversion proposed by Mendiguren instead of the time domain inversions of the other investigators.…”
Section: H Patton and K Akimentioning
confidence: 99%
“…In light of the evidence summarized by Aki (1967Aki ( , 1972 and Chouet, Aki & Tsujiura (1978), the step function assumption is valid for periods longer than 20s when the magnitude of the source is six or less.…”
Section: A$ the Real Part Is Re { S ) -A$im { S ) And The Imaginary mentioning
confidence: 99%
See 1 more Smart Citation
“…The first application of the linear inversion was carried out by Dziewonski and Gilbert (1974) on free oscillation datasets for two deep shocks in South America. Extensions of this method to other datasets have been proposed by a number of investigators (Buland and Gilbert, 1976;McCowan, 1976;Mendiguren, 1977).…”
Section: Linear Inversion For the Seismic Moment Tensormentioning
confidence: 99%